2013
DOI: 10.1165/rcmb.2012-0229oc
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Rescues Alveolar Hypoplasia in the Calorie-Restricted Developing Rat Lung

Abstract: Infants born with intrauterine growth retardation (IUGR) are at increased risk of adverse pulmonary outcomes at birth, including meconium aspiration and persistent pulmonary hypertension. Preterm infants with IUGR are at especially high risk of developing bronchopulmonary dysplasia (BPD), a disease hallmarked by alveolar hypoplasia. Although vitamin A supplementation has been shown to decrease the incidence of BPD or death in preterm very low birth weight infants, its potential to reduce BPD or death in preter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Of note, a small cohort of the Mmp14 −/− mice (3 of 15 total) displayed an unusually reduced body size with partial mammary gland defects noted at P10 (the mammary ducts branched comparably, but appeared more primitive in their architecture). However, given the reduced feeding of this cohort and the known influence of nutrient deprivation on tissue morphogenesis (Londhe et al, 2013), we did not include these animals in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a small cohort of the Mmp14 −/− mice (3 of 15 total) displayed an unusually reduced body size with partial mammary gland defects noted at P10 (the mammary ducts branched comparably, but appeared more primitive in their architecture). However, given the reduced feeding of this cohort and the known influence of nutrient deprivation on tissue morphogenesis (Londhe et al, 2013), we did not include these animals in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the postnatal growth restriction resulting from insufficient total calories that is commonly observed in premature infants 98, 99 may represent an additional risk factor 100 , with evidence suggesting that adequate intake of protein 101 , fat 102 , and specific vitamins 103106 are particularly important. Data from animals models 107109 suggest that pre- and postnatal growth restriction alters antioxidant activity 110 , surfactant production 111 , pulmonary endothelial function 112 , and biologic pathways that regulate pulmonary vascular growth 113 . Despite these broad effects on key developmental pathways, recent clinical trials to optimize nutrition in preterm infants have demonstrated little or no impact on the incidence of BPD 114117 , with the exception of Vitamin A supplementation, which is associated with a small decrease in the risk of developing BPD 118 .…”
Section: Injurious Stimuli That Disrupt Late Lung Developmentmentioning
confidence: 99%
“…19 We recently reported, in a novel rat model of IUGR through maternal calorie restriction, that vitamin A supplementation was able to rescue alveolar development in both pre- and postnatally calorie restricted offspring. 20 Importantly, this rodent model has applicability to preterm human infants because term newborn rats are born with lung development equivalent to that of 26- to 28-week preterm human infants. 19 These findings are thus highly relevant to the current subgroup analysis in exploring whether vitamin A supplementation demonstrates improved pulmonary outcomes in preterm human infants who are SGA (and possibly IUGR).…”
Section: Discussionmentioning
confidence: 99%